Fabrication, Microstructural, and Mechanical Behavior of SiC Composite with Insitu Formation of BN and Si3N4 - Singh A.; Singh V.K.; Chaturvedi R.K.; Kumari J.; Debnath N.K. (My University, 2025)
Dealing with high-temperature properties and brittleness and is always one of the hot topics in the field of ceramic materials. Extensive research has been carried out for it and Si3N4-SiC composites are one of the most promising composites. In this study, the impact of Si3N4 and BN reinforcement on the microstructure and physio-mechanical properties of SiC-based composites were explored. Two sets of composites, including Si3N4-SiC and BN-Si3N4-SiC aided with Al2O3, were fabricated using nitridation of Si and B2O3 at 1450 °C. The mechanical properties, microstructure, phase transformation, densification, and porosity were depicted and discussed. X-ray diffraction patterns revealed the insitu formation of Si3N4 (both α and β phases) and BN in the final composite. The specimen with 10% Si and 10% B2O3 possessed the superior flexural strength (284.4 MPa) with excellent hardness (23.4 GPa). The incorporation of BN is found to enhance the mechanical properties especially hardness while overcoming the shortcomings of reaction-bonded Si3N4-SiC. The corresponding densification and strengthening mechanism were explained in this paper. © 2023, The Author(s), under exclusive licence to Springer Nature B.V.